CD4+ T‐cell subsets in intestinal inflammation. Issue 1 (13th February 2013) - Shale, Matthew; Schiering, Chris; Powrie, Fiona
Summary: Intestinal CD4 + T cells are essential mediators of immune homeostasis and inflammation. Multiple subsets of CD4 + T cells have been described in the intestine, which represents an important site for the generation and regulation of cells involved in immune responses both within and outside of the gastrointestinal tract. Recent advances have furthered our understanding of the biology of such cells in the intestine. Appreciation of the functional roles for effector and regulatory populations in health and disease has revealed potential translational targets for the treatment of intestinal diseases, including inflammatory bowel disease. Furthermore, the role of dietary and microbiota‐derived factors in shaping the intestinal CD4 + T‐cell compartment is becoming increasingly understood. Here, we review recent advances in understanding the multifaceted roles of CD4 + T cells in intestinal immunity.